IMPROVING STUDENT’S READING COMPREHENSION THROUGH COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) ON ACCOUNTING STUDENTS IN TRIATMA MULYA UNIVERSITY - Ernila Junipisa, Ni Made; Purnami, Ni Made Ayu (Program Studi Pendidikan Bahasa Indonesia dan Daerah Universitas PGRI Mahadewa Indonesia, 2023)
This research is aimed to find out whether or not the implementation CIRC during students’ learning activities. The participant of this research was 30 students in accounting class in Triatma Mulya University. The required data were collected through the use of questionnaire, observation checklist, and reading test. The data from the questionnaire indicated that students had positive attitude toward the implementation of CIRC. CIRC improves their reading comprehension in learning English and this technique brings more fun to the process of learning. Moreover, it was found from observation data that the students were actively participated during the implementation. Finally, the study proved that CIRC improved students’ reading comprehension Students’ mean score of reading before implemented this technique was 56.06 in the beginning of the study the mean score was 71.2 their mean scores improved from 77,94 to 85,23. Keywords: CIRC ,Reading Comprehension , Accounting Students